Phenology and polyploidy in annual Brachypodium species (Poaceae) along the aridity gradient in Israel. Issue 2 (1st May 2019) - Penner, Shira; Dror, Barak; Aviezer, Iris; Bar‐Lev, Yamit; Salman‐Minkov, Ayelet; Mandakova, Terezie; Šmarda, Petr; Mayrose, Itay; Sapir, Yuval
Abstract: Local adaptation of plants along environmental gradients provides strong evidence for clinal evolution mediated by natural selection. Plants have developed diverse strategies to mitigate stress, for example, drought escape is a phenological strategy to avoid drought stress, while polyploidy was proposed as a genomic adaptation to stress. Polyploidy as an adaptation to aridity (an environmental parameter integrating temperature and precipitation) was previously documented in annual Brachypodium spp. (Poaceae) in the Western Mediterranean. Here, we examined whether polyploidy or phenology are associated with aridity in annual Brachypodium spp. along the aridity gradient in the Eastern Mediterranean. Using flow cytometry, we determined ploidy levels of plants from natural populations along the Israeli gradient, spanning ∼424 km from mesic Mediterranean to extreme desert climates. In a common garden we recorded time of seedling emergence, flowering and senescence. We tested whether the proportion of allotetraploids in the populations and phenological traits were associated with aridity. Contrary to a previous study in the Western Mediterranean, we found no effect of aridity on the proportion of allotetraploids and diploids within populations. Interestingly, phenology was associated with aridity: time of emergence was later, while flowering and senescence were earlier in desert plants. Our results indicate that in the Eastern Mediterranean, adaptation of Brachypodium to aridity is mediated mainly by phenology, rather than ploidy level. Therefore, we suggest that genome duplication is not the main driver of adaptation to environmental stress; rather, phenological change as a drought escape mechanism may be the major adaptation.